De novo 12q22.q23.3 duplication associated with temporal lobe epilepsy. (April 2018) - Stella Vari, Maria; Traverso, Monica; Bellini, Tommaso; Madia, Francesca; Pinto, Francesca; Striano, Pasquale; Minetti, Carlo; Zara, Federico
Abstract : The Publisher regrets that this article is an accidental duplication of an article that has already been published in Seizure 50 (2017) 80–82, http://dx.doi.org/10.1016/j.seizure.2017.06.011 . The duplicate article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found athttps://www.elsevier.com/about/our-business/policies/article-withdrawal